Parental Social Support for Children Participating in Push Bike Sports - Melly Nataly; Fery Darmanto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to explore and describe parental social support for children par-ticipating in push bike sports in Pati Regency. This study uses a mixed-methods approach combining quantitative and qualitative methods. The research sample consisted of 15 children aged 2-5 years who actively participated in push bike training and competitions and were accompanied by their parents. The data col-lection techniques used were questionnaires and structured interviews. Quantita-tive data were analyzed using SPSS through descriptive statistical techniques, in-cluding mean, percentage, standard deviation, and graphical presentations. Inter-view data were analyzed using NVivo through transcription, thematic coding, and data visualization using Word Frequency Query and Project Map.  The findings indicate that children participating in push bike sports receive high levels of social support from parents, coaches, and peers. The descriptive statistics show a mean of 45.71 and a social support percentage of 84.64%, which falls within the high category. Emotional support emerged as the most dominant aspect, contributing to children's sense of security, comfort, and confidence during training and com-petitions. Furthermore, instrumental support, such as providing facilities, fund-ing, and training assistance, also contributes to the sustainability of children's sports activities.